Demanding sex : critical reflections on the regulation of prostitution - Della Giusta, Marina, 1970-; Munro, Vanessa (Ashgate, 2008)
Interrogating supply/demand from an inter- and multi-disciplinary perspective, this collection focuses on the supply/demand dynamic of prostitution. It brings into play a range of other societal, economic and psychological factors such as the social construction of sexuality, the viability of alternative choices for prostitutes and clients, and the impact of regulatory regimes on the provision of sexual services.